1995
DOI: 10.2138/am-1995-3-413
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of microanalytical methods for estimating H2O contents of silicic volcanic glasses

Abstract: Three methods of estimating H20 contents of geologic glasses are compared: (1) ion microprobe analysis (secondary ion mass spectrometry), (2) Fourier-transform infrared spectroscopy (FTIR), and (3) electron microprobe analysis using the Na decay-curve method. Each analytical method has its own advantages under certain conditions, depending on the relative importance of analytical accuracy, precision, sensitivity, spatial resolution, and convenience, and each is capable of providing reasonably accurate estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
166
0
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(174 citation statements)
references
References 11 publications
7
166
0
1
Order By: Relevance
“…Other elements were calibrated on natural and synthetic mineral standards. EPMAs for hydrous rhyolitic reference glasses are presented in Table 2 and show excellent agreement with previously published values [Devine et al, 1995]. showed that unless additional corrections are applied, the indirect methods will yield erroneously high results.…”
Section: Methodssupporting
confidence: 86%
“…Other elements were calibrated on natural and synthetic mineral standards. EPMAs for hydrous rhyolitic reference glasses are presented in Table 2 and show excellent agreement with previously published values [Devine et al, 1995]. showed that unless additional corrections are applied, the indirect methods will yield erroneously high results.…”
Section: Methodssupporting
confidence: 86%
“…The pre-eruptive volatile content of a rock can be approximated from the mass deficiency in EMP analyses of groundmass glass and melt inclusions ("the difference method"), as described in Devine et al (1995), provided that the volatiles make up >1%. Anak Krakatau melt inclusions represent the melt composition of the magma during different stages of its evolution prior to degassing and eruption.…”
Section: Pre-eruptive H 2 O Contentmentioning
confidence: 99%
“…The mass deficiency in the glass inclusions measured here ranges from 1.2 to 4.9 wt% (average = 2.4 wt%; n = 9). However, the precision of the "difference method" is not very high (generally around ±0.5 %; Devine et al 1995). Mandeville et al (1996a), also using the "difference method", estimated the pre-eruptive volatile content in 1883 Krakatau rhyolites and dacites to be 4 ± 0.5 wt.…”
Section: Pre-eruptive H 2 O Contentmentioning
confidence: 99%
“…In this paper the effects of fo2 and melt H20 content on <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 +1 <1 <1 <1 <1 <1 <1 -1 <1 <1 <1 +1 -1 <1 <1 <1 -1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 <1 3.96 + 1 g1(75), pl(16), opx(6), mt(3), ame 0.21 < 1 g1(66), p1(24), opx(7), mt(3), ame 0.63 < 1 gl(60), pl(30), opx(7), mt(3), ame 0.12 < 1 g1(95), pl(1), mt(4), ame 2.75 < 1 g1(63), p1(29), opx(6), mt(2), ame 0.15 < 1 g1(62), p1(28), opx(7), mt(3), ame 1.03 < 1 g1(59), pl(31), opx(5), cpx(3), mt(2), ame 0.57 < 1 all20 calculated from H20 in glass using the model of Burnham [1979] (see also text); log fo2 calculated from experimental fH2 (see text) and calculated fH20 (obtained from aH20); ANNO = log fo2 -log fo2 of the NNO buffer calculated at P and T [Chou, 1987] (Table 2), infrared spectroscopy could not be used as a routine method for H20 analysis. The glass H20 contents were thus measured using the "by-difference" method [Devine et al, 1995]. The difference from 100% of electron microprobe analyses (after correction of the alkalies) was calibrated against the dissolved glass H20 content by using the three hydrous glasses described above as standards, analyzed together with the experimental glasses during each microprobe session.…”
Section: 453mentioning
confidence: 99%